البيئة اللغوية وتأثيرها في تحسين مهارة الكلام لغير الناطقين بالعربية بوصفها لغة ثانية The linguistic environment and its effect on improving speech skill for non-Arabic speakers as a second language. The linguistic environment and its effect on improving speech skill for non-Arabic speakers as a second language - Ali, Asem Shehadeh Saleh (Department of Arabic Language and Literature (DALL), 2020)
إن مهارة الكلام لها عناصر معينة، ومن تلك العناصر هو اللسان والصوت، فاللسان أداة البيان وقال تبارك وأما البيئة اللغوية فهي أحد المداخل التعليمية التي ترقّي كفاءة مهارة الكلام لدى الدارس في اللغة الثانية باستفادة البيئة بوصفها مصدر التعلم، فيتمكن المتعلم من الاستخدام العلمي العملي لمهارة الكلام لحسن استغلال البيئة والاستفادة من إمكاناتها، فالإنسان يتفاعل مع البيئة التي يعيش فيها عن طريق عملية التأثير والتأثر طبيعياً، فيأخذ الإنسان من بيئته ويعطيها سواء أكانت مادية مثل العوامل والظروف الجغرافية والمناخية، أم إنسانية مثل العوامل النفسية. وأما العينات في هذا البحث، فهم من طلبة الدراسات العليا بالجامعة الإسلامية العالمية بماليزيا في الدراسات العربية والإسلامية، ونختار هذه الجامعة لأسباب عدة، منها: أنها من أشهر الجامعات التي تشجع الطلبة على تعلم العربية، ويضيق البحث نطاق بحثه إلى طلبة الدراسات العربية والإسلامية؛ لأنهم يعتمدون على اللغة العربية أكثر من التخصصات الأخرى، فيكون هذا البحث يسير على الواقع. ويستخدم البحث المنهج الوصفي والتحليلي للحصول على معلومة دقيقيه له وللقارئ؛ والوقوف على ملامح البيئة اللغوية ومهارة الكلام لدى العينات يستلزم وصفاً لهما، وتحليلاً لتلك الملامح والبيانات من الاستبانة للوصول إلى نتائج مهمة. The skill of speech has certain elements, and among these elements is the tongue and sound, for the tongue is the instrument of rendering and the blessed one said. The linguistic environment one of the educational approaches that promotes the efficiency of the speech skill of the learner in the second language. It uses of the environment as the source of learning. The learner can use the practical scientific skills of speech to make good use of the environment and take advantage of its capabilities. The human being interacts with the environment in which he lives through the process of influencing and influencing naturally, a person takes from his environment and gives it whether it is material like geographical and climatic factors and conditions, or human like psychological factors. As for the samples in this research, they are from graduate students at the International Islamic University in Malaysia in Arab and Islamic studies. We choose this university for several reasons, including: It encouraging students to learn Arabic, and the research narrows the scope of its research to students of Arab and Islamic studies; because they rely on the Arabic language more than other disciplines, so this research is going on. The research uses the descriptive and analytical method to obtain accurate information for him and the reader. In addition, knowing the features of the linguistic environment and speech skill of the samples requires a description of them, and an analysis of these features and data from the questionnaire to reach important results.